Attractiveness of Leg Length : report From 27 Nations - Sorokowski, Piotr; Szmajke, Andrzej; Sorokowska, Agnieszka; Cunen, Maryann Borg; Fabrykant, Marharyta; Zarafshani, Kiumars; Amiri, Manochehr; Bazzazian, Saeideh; Blazevska-Stoilkovska, Biljana; Casellas, Veronica; Cetinkaya, Hakan; Coutino, Berenice Lopez; et al. (2011)
The leg-to-body ratio (LBR) is a morphological index that has been shown to influence a person’s attractiveness. In our research, 3, 103 participants from 27 nations rated the physical attractiveness of seven male and seven female silhouettes varying in LBR. We found that male and female silhouettes with short and excessively long legs were perceived as less attractive across all nations. Hence, the LBR may significantly influence perceptions of physical attractiveness across nations.
Projekt MZOS
ENG